Drug Expenditure Trends in the Canadian Provinces: Magnitude and Causes from 1998 to 2004 - Morgan, Steve (Longwoods Publishing, 2005)
This analysis uses a consistent pan-Canadian dataset – Canadian CompuScript from IMS Health, Canada – to quantify trends in per capita drug expenditures within each Canadian province over the period of 1998 to 2004. The impacts of changes in six potential determinants of drug expenditure are calculated for every province. Each of the six detailed cost drivers falls into one of three broad categories: volume effects, price effects and therapeutic choices. Despite wide variation in expenditure levels, the rate and causes of provincial expenditure trends over time were roughly comparable. From 1998 to 2004, per capita expenditures on oral solid prescription drugs grew at a rate of over 10% per year in most provinces – several times faster than economic growth over the same period. This rapid expenditure growth has largely been due to increased utilization of medicines and a trend towards prescribing higher-cost drugs over time. Price changes had little impact on drug spending in all provinces.